2021
DOI: 10.1007/s41781-020-00052-w
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Distribution of High-Rate Data Processing from CERN to Remote HPC Data Centers

Abstract: The prompt reconstruction of the data recorded from the Large Hadron Collider (LHC) detectors has always been addressed by dedicated resources at the CERN Tier-0. Such workloads come in spikes due to the nature of the operation of the accelerator and in special high load occasions experiments have commissioned methods to distribute (spill-over) a fraction of the load to sites outside CERN. The present work demonstrates a new way of supporting the Tier-0 environment by provisioning resources elastically for suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Integration of HPCs that are transparent to central computing operations have been performed in several countries in Europe, e.g., Italy, Switzerland, Germany, and Spain, for example expanding existing Tier 1 or Tier 2 sites elastically into these machines [350][351][352], or by deploying so-called overlay batch systems [353]. It is also through this model that a validation of the physics performance of CMS software on the PowerPC architecture could be performed [354].…”
Section: High Performance Computing (Hpc)mentioning
confidence: 99%
“…Integration of HPCs that are transparent to central computing operations have been performed in several countries in Europe, e.g., Italy, Switzerland, Germany, and Spain, for example expanding existing Tier 1 or Tier 2 sites elastically into these machines [350][351][352], or by deploying so-called overlay batch systems [353]. It is also through this model that a validation of the physics performance of CMS software on the PowerPC architecture could be performed [354].…”
Section: High Performance Computing (Hpc)mentioning
confidence: 99%
“…Nevertheless, using the vCluster approach, we can extend the HPC cluster configuration to an extreme data-driven HTC cluster configuration, and customise recipes for user access, slurm controls and software-defined, multi-tenant, HTC-oriented file systems. Previous studies have demonstrated that the middleware for virtualised computing and storage stacks aren’t interoperable with classic, Petascale supercomputing systems (De et al, 2021) (Boccali et al 2021). The middleware has been partially containerised (Roy et al, 2020).…”
Section: Wlcg Platform Vclusters On Alpsmentioning
confidence: 99%
“…Remote computing interfaces: Many customized solutions have been developing for linking scientific instruments with HPC, for example in biomedicine [82], environmental science [83,84], and disaster response [85,86]; using HPC to analyze large data [87]; and providing on-demand access to HPC [88,89]. Such applications have motivated the development of specialized interfaces for remote job submission [90,91] and for managing workloads across systems [92][93][94][95].…”
Section: Related Workmentioning
confidence: 99%